THE ROLE OF QUALITY LIFE AS A MEDIATION EFFECT OF PERCEIVED VALUE AND TOURIST SATISFACTION ON BEHAVIOURAL INTENTION - Berutu, Meta Bara; Rohman, Fatchur; Sabil, Ananda (Universitas Brawijaya, Indonesia, 2022)
Tourism is one of the fastest-growing industries in the world. It is one of the engines of global development, including in Indonesia. This research will look at important aspects that can influence tourist behavior concerning tourism places. The respondents of this research were tourists who had visited Bromo Mount using the purposive sampling technique with a total sample of 240 respondents. The method of data collection is using questionnaires and data analyzed with PLS-SEM. The results showed that perceived value and tourist satisfaction had a significant positive effect on behavioral intention. The quality of life can be a mediator between the independent and dependent variables. Quality of life is one aspect that can be improved from the emotional side that influences many aspects so that tourists can revisit the intention and word of mouth of Bromo Mount to meet the specified tourist targets. Furthermore, researchers are expected to do more extensive research by considering the aspect of QoL at the family, community, and country level.